2014
DOI: 10.1080/15248372.2014.888350
|View full text |Cite
|
Sign up to set email alerts
|

Specifying Links Between Executive Functioning and Theory of Mind during Middle Childhood: Cognitive Flexibility Predicts Social Understanding

Abstract: for comments on earlier versions of this paper. We also thank the children and parents who participated. Portions of this research were supported by the Graduate School and by a Summer Faculty Fellowship from Illinois State University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 57 publications
(84 reference statements)
7
68
1
1
Order By: Relevance
“…In general, the results of the correlation and cluster analysis indicate that there is a relationship between the level of a child's understanding of false beliefs and such components of cognitive control as inhibition and switching, which is in good agreement with the previous studies (Bock et al, 2015;Cantin et al, 2016;Carlson et al, 2015;Muller et al, 2012;Perner et al, 2002;Yeniad et al, 2013). Most authors hold the view that this relationship stems from the participation of executive functions in performing false belief tasks: a child should be flexible enough to switch between its belief and another person's vision of the situation, and also to suppress its own knowledge about the situation.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In general, the results of the correlation and cluster analysis indicate that there is a relationship between the level of a child's understanding of false beliefs and such components of cognitive control as inhibition and switching, which is in good agreement with the previous studies (Bock et al, 2015;Cantin et al, 2016;Carlson et al, 2015;Muller et al, 2012;Perner et al, 2002;Yeniad et al, 2013). Most authors hold the view that this relationship stems from the participation of executive functions in performing false belief tasks: a child should be flexible enough to switch between its belief and another person's vision of the situation, and also to suppress its own knowledge about the situation.…”
Section: Resultssupporting
confidence: 79%
“…Modern research confirms that theory of mind develops rapidly in early childhood (Frye et al, 1995;Hughes, 1998;Wellman, & Liu, 2004) and continues to improve throughout the preschool and primary school years (Apperly et al, 2011;Bock et al, 2015;Happé, 1994;Miller, 2009;Miller, 2012;White et al, 2009). Significant changes in theory of mind development occur at an older preschool age: at the age of 5-6 there is a transition to the level, when one's own mental model can not only be separated from the model of the mental Other, but there arises a possibility to mentally influence it, the model becomes situationally independent (Wimmer, & Perner, 1983).…”
Section: Theory Of Mindmentioning
confidence: 91%
See 2 more Smart Citations
“…It is thought that consideration of others is based on theory of mind, that is, understanding of their own and other individuals' mental states. EfC refers to the ability to inhibit a dominant response in order to perform a subdominant response (Rothbart, 2011 self-regulation) was significantly related to theory of mind in toddler and preschool children (Carlson and Moses, 2001;Carlson et al, 2004;Sabbagh et al, 2006;Hughes and Ensor, 2007;Korucu et al, 2017), and middle childhood (aged 7-12 years old) (Bock et al, 2015). In this study, we confirmed a similar trend in early and middle adolescence.…”
Section: Discussionsupporting
confidence: 78%